2015
DOI: 10.1089/jamp.2014.1159
|View full text |Cite
|
Sign up to set email alerts
|

A Handling Study to Assess Use of the Respimat® Soft Mist™ Inhaler in Children Under 5 Years Old

Abstract: Background: Respimat® Soft Mist™ Inhaler (SMI) is a hand-held device that generates an aerosol with a high, fine-particle fraction, enabling efficient lung deposition. The study objective was to assess inhalation success among children using Respimat SMI, and the requirement for assistance by the parent/caregiver and/or a valved holding chamber (VHC).Methods: This open-label study enrolled patients aged <5 years with respiratory disease and history of coughing and/or recurrent wheezing. Patients inhaled from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 17 publications
0
22
0
4
Order By: Relevance
“…The Respimat ® , which is currently the only commercially available soft mist inhaler, contains a mechanical spring that atomizes the drug solution, creating a fine, slow-moving mist with a relatively higher deposition in the lung, and less drug deposited in the mouth and throat [29]. A recent handling study of the Respimat ® in children under 5 years old found that all children using the Aero-Chamber Plus ® Flow-Vu ® VHC and face mask, either by themselves or with adult assistance, achieved successful handling, and thus recommended that a VHC should be used to administer tiotropium via the Respimat ® in children younger than 5 years old [19]. In addition to ensuring correct handling of the device, there is also a need for safety and optimal clinical control of aerosol delivery in children, and for a realistic prediction of the dose delivered to the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Respimat ® , which is currently the only commercially available soft mist inhaler, contains a mechanical spring that atomizes the drug solution, creating a fine, slow-moving mist with a relatively higher deposition in the lung, and less drug deposited in the mouth and throat [29]. A recent handling study of the Respimat ® in children under 5 years old found that all children using the Aero-Chamber Plus ® Flow-Vu ® VHC and face mask, either by themselves or with adult assistance, achieved successful handling, and thus recommended that a VHC should be used to administer tiotropium via the Respimat ® in children younger than 5 years old [19]. In addition to ensuring correct handling of the device, there is also a need for safety and optimal clinical control of aerosol delivery in children, and for a realistic prediction of the dose delivered to the lung.…”
Section: Discussionmentioning
confidence: 99%
“…A previous in vitro study using throat models of children approximately 5 years old found that the use of the AeroChamber Plus ® Flow-Vu ® VHC for administering tiotropium Respimat ® provided optimal dose-to-lung (DTL) in comparison with other VHCs, whilst minimizing retention at throat level [17]. Patients over the age of 5 years who are able to exhibit proper inhaler technique have been reported as having effective clinical outcomes following use of the Respimat ® without a VHC [18]; moreover, children younger than 5 years can handle the Respimat ® well when using a suitable VHC to complement its use [19].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, handling studies of the Respimat device recommend the addition of a VHC in children Յ5 y old. 8 The Respimat with a VHC effectively delivered aerosol to a group of sleeping infants. 9 Due to the paucity of clinical studies, most of our insight on optimization of aerosol delivery with pMDIs and VHCs through tracheostomy derives from in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…A study assessing handling and inhalation flow profiles found that all children aged \5 years could achieve inhalation success with basic training and assistance from a parent/caregiver [43]. The assessment of the theoretical dose delivered to the lung from inhalation flow profiles has been shown to confirm and complement pharmacokinetic analyses conducted in clinical trials of children of the same age group with cystic fibrosis [44].…”
Section: Patient-centered Design Innovationmentioning
confidence: 93%
“…It provides efficient drug delivery in pediatric patients [37,43,55], including children \5 years when using a spacer [27,43]. In one study, anecdotal evidence suggested that children aged 6-15 years found it easy to learn how to use Respimat Ò and preferred this inhaler to using an MDI [37].…”
Section: Respimatmentioning
confidence: 99%